Prime time violence [videorecording] - Harris, Bob.; Kurtis, Bill.; Stoner, Barry; Arts and Entertainment Networks (New York, N.Y.).; Kurtis Productions Ltd. (New York Kurtis Productions & A%E Networks, 1994)
The ever-growing incidence of violence on television is examined. Includes debates of producers, politicians and parents over television violence. It takes a look at U.S. government censorship and the future of TV violence.
VHS.
Credits : Editor, John Anderson.
Keywords: Violence in television -- United States; Firearms -- United States; Television -- Censorship; Violence in mass media -- Law and legislation -- United States; Violence in mass media -- United States